2019
DOI: 10.1007/s40881-019-00068-y
|View full text |Cite|
|
Sign up to set email alerts
|

Do people exploit risk–reward structures to simplify information processing in risky choice?

Abstract: The high rewards people desire are often unlikely. Here, we investigated whether decision-makers exploit such ecological correlations between risks and rewards to simplify their information processing. In a learning phase, participants were exposed to options in which risks and rewards were negatively correlated, positively correlated, or uncorrelated. In a subsequent risky choice task, where the emphasis was on making either a 'fast' or the 'best' possible choice, participants' eye movements were tracked. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…There is growing evidence that people use the risk–reward heuristic to infer missing probabilities and missing payoffs, which in turn impacts the choices they make (Hoffart, Rieskamp, & Dutilh, 2018; Leuker, Pachur, Hertwig, & Pleskac, 2018; Pleskac & Hertwig, 2014; Skylark & Prabhu-Naik, 2018). The risk–reward structure also impacts other aspects of decision making, including how people evaluate options with known probabilities (Leuker, Pachur, Hertwig, & Pleskac, 2019a, 2019b). Enlisting an environmental structure like the risk–reward structure—be it via a heuristic or within a larger framework, such as Bayesian inference (e.g., Chater, Oaksford, Hahn, & Heit, 2010; Gershman, Horvitz, & Tenenbaum, 2015; Griffiths, Chater, Kemp, Perfors, & Tenenbaum, 2010) or reinforcement learning (e.g., Daw, Niv, & Dayan, 2005; Niv, 2009)—is appealing because it requires relatively little time and effort; decision makers can instead invest more of their limited resources in seeking out other information or achieving other goals.…”
mentioning
confidence: 99%
“…There is growing evidence that people use the risk–reward heuristic to infer missing probabilities and missing payoffs, which in turn impacts the choices they make (Hoffart, Rieskamp, & Dutilh, 2018; Leuker, Pachur, Hertwig, & Pleskac, 2018; Pleskac & Hertwig, 2014; Skylark & Prabhu-Naik, 2018). The risk–reward structure also impacts other aspects of decision making, including how people evaluate options with known probabilities (Leuker, Pachur, Hertwig, & Pleskac, 2019a, 2019b). Enlisting an environmental structure like the risk–reward structure—be it via a heuristic or within a larger framework, such as Bayesian inference (e.g., Chater, Oaksford, Hahn, & Heit, 2010; Gershman, Horvitz, & Tenenbaum, 2015; Griffiths, Chater, Kemp, Perfors, & Tenenbaum, 2010) or reinforcement learning (e.g., Daw, Niv, & Dayan, 2005; Niv, 2009)—is appealing because it requires relatively little time and effort; decision makers can instead invest more of their limited resources in seeking out other information or achieving other goals.…”
mentioning
confidence: 99%
“…These expectations can stem from regularities in the environment, such as larger rewards are less likely to be received than smaller rewards (Pleskac & Hertwig, 2014). There is evidence that people make use of this relation as participants take longer to make choices and show higher levels of attention (measured by eye-tracking) when lotteries are atypical and do not follow this risk-reward regularity in DfD (Leuker et al, 2019). Similarly, probability judgments as well as search patterns in DfE have shown that people usually assume a negative relation between probability and outcome (Hoffart et al, 2019).…”
Section: Learning and Pattern Recognitionmentioning
confidence: 99%
“…Several articles in this special issue discuss SSMs in detail, with connections to random utility theory (Smith et al 2019), risky decision-making (Leuker et al 2019), and distinguishing between effort and ability (Alekseev 2019). Another article (Gawryluk and Krawczyk 2019) investigates changes of mind over time.…”
Section: Response Timesmentioning
confidence: 99%
“…In this special issue, Smith et al (2019) provide a simple method for estimating this effect of gaze on choice, using standard logistic regression. Another article examines similar SSM gaze effects in risky choice (Leuker et al 2019). A third article also examines dwell-time effects in risky choice, albeit within a different modeling framework (Harrison and Swarthout 2019).…”
Section: Eye Movementsmentioning
confidence: 99%